The Influence of Marketing Mix and Trust on Smartphone Brand Switching - Ainun Mardhiyah; Feby Aulia Safrin (LifeSciFi, 2023)
Brand switching is a familiar thing in our daily lives. This study aims to analyze how products can affect smartphone brand switching for teenagers in Medan City and also to analyze how prices can affect smartphone brand switching for teenagers in Medan City and to analyze how promotions can affect smartphone brand switching for teenagers in Medan City and to analyze how brand trust can affect smarphone brand switching among teenagers in Medan City and to find out whether there is an influence of Marketing Mix (Product, Price and Promotion) and also brand trust on brand switching by consumers so that companies can take steps to avoid brand switching by consumers. The method used in this research is descriptive qualitative method with interviews and Focus Group Discussions (FGD) and also quantitative method by distributing questionnaires. The results of this study are that the marketing mix (product, price and promotion) affects smartphone brand switching by teenagers in Medan City, and also teenagers’ brand trust in smartphone brands affects smartphone brand switching by teenagers in Medan City. The output of this research will be international journals and national journals